Meta-surface (frequency selective surface) loaded high gain directional antenna systems for ultra-wideband applications - Mohammed Amer Hamed AL-shamili; Madan Kumar Sharma (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In this work, a meta-surface (frequency selective surface) loaded high gain directional antenna system is presented. The antenna system is developed using ultra-wideband (UWB) antenna element and meta-surface reflector. The UWB antenna element is designed and simulated without meta-surface reflector. The UWB antenna element has poor impedance bandwidth and directivity. A meta-surface is created using unit cell and equal in the size of the antenna substrate. The meta-surface is placed over the UWB antenna element at optimized height (H=30 mm). The impedance bandwidth, directivity and gain of the proposed antenna are improved by the meta-surface reflector. The proposed antenna is fabricated and experimentally validated by the comparison of the simulated and measured results. The antenna has 3 to 6 GHz wide impedance bandwidth, more than 5 dBi gain and maximum 4.6 dBi directivity at 3.5 GHz frequency. Performance of the proposed antenna is also compared with existing carried out work. Comparatively, the proposed antenna with high directivity is most suitable for IEEE 802.15.4a UWB wireless sensor network (WSN) security application.